Inovasi Pengembangan Produk Herbal Clitoria Ternatea Sebagai Optimalisasi Pemanfaatan Potensi Lokal - Runik Puji Rahayu; Rani Nur Fitrianti; Devi Lestari Pramita Putri; Rohmaniyah Rohmaniyah; Nurul Alfian (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This service activity aims to add innovation to Clitoria Ternatea herbal products in the ASMANTOGA PKK group, Ceguk village, Pamekasan district. These wild plants are very often found in the environment around people's lives, one of which is currently very popular is the telang flower which we know by the Latin name Clitoria Ternatea. This activity provides product innovation made from butterfly pea flowers. The methods used are demonstration methods, socialization methods, and training methods. The result of this activity is education regarding innovation in the development of Clitoria Ternatea herbal products as an optimization of the utilization of local potential in Ceguk village, Pamekasan district. Apart from that, participants were able to understand the training methods for developing Clitoria Ternatea herbal products as processed drinks for the community in Ceguk village, Pamekasan district through PKK women.